Measurements of shoaling internal waves and turbulence in an estuary. Issue 1 (30th January 2013) - Richards, Clark; Bourgault, Daniel; Galbraith, Peter S.; Hay, Alex; Kelley, Dan E.
Abstract: [1] The shoaling of horizontally propagating internal waves may represent an important source of mixing and transport in estuaries and coastal seas. Including such effects in numerical models demands improvements in the understanding of several aspects of the energetics, especially those relating to turbulence generation, and observations are needed to build this understanding. To address some of these issues in the estuarine context, we undertook an intensive field program for 10 days in the summer of 2008 in the St. Lawrence Estuary. The sampling involved shore‐based photogrammetry, ship‐based surveys, and an array of moorings in the shoaling region that held both conventional and turbulence‐resolving sensors. The measurements shed light on many aspects of the wave shoaling process. Wave arrivals were generally phase‐locked with the M 2 tide, providing hints about far‐field forcing. In the deeper part of the study domain, the waves propagated according to the predictions of linear theory. In intermediate‐depth waters, the waves traversed the field site perpendicularly to isobaths, a pattern that continued as the waves transformed nonlinearly. Acoustic Doppler velocimeters permitted inference of the turbulent energetics, and two main features were studied. First, during a period of shoaling internal waves, turbulence dissipation rates exceeded values associated with tidal shear by an order of magnitude. Second, the evolving spectral signatures associated with a particular wave‐shoaling event suggest that the turbulence is at least partly locally generated. Overall, the results of this study suggest that parameterizations of wave‐induced mixing could employ relatively simple dynamics in deep water, but may have to handle a wide suite of turbulence generation and transport mechanisms in inshore regions. Key Points: Internal waves were successfully tracked with a dense instrument array Dissipation rates during wave shoaling are higher than tidal shear predictions An energy budget suggests that internal wave mixing may be important overall